Analysis of fracture behavior of high-strength steels in tension after fire exposure. (15th March 2021) - Cai, Wen-Yu; Jiang, Jian; Wang, Yan-Bo; Li, Guo-Qiang
Highlights: Post-fire fracture models of high strength steels Q460, Q550, Q690, Q890 S460, S690, S960 are proposed. The true stress-strain curve, toughness index in SMCS model and damage evolution law are calibrated. The maximum exposure temperature and cooling method are two critical influencing factors. Different high-strength steels with similar yield strength may exhibit different post-fire fracture behavior. The water-cooling method may lead to change from ductile fracture mode to brittle fracture mode. Abstract: High-strength steels have been widely applied in high-rise and long-span structures. Exposure to high temperatures due to fire may lead to reduction in material properties and fracture behavior of high-strength steels, greatly affecting the post-fire behavior of high-strength steel structures. This paper investigates the post-fire fracture behavior of high-strength steels in tension to pave the way for safety assessment of high-strength steel structures after fire. The fracture models of Chinese high-strength steels (Q460, Q550, Q690, Q890) and European high-strength steels (S460, S690 and S960) are calibrated and validated against limited experimental results of tensile coupon tests in an exposure temperature range of 200 °C to 1000 °C. The effect of air-cooling and water-cooling methods on the post-fire fracture behavior of high-strength steels is investigated. The fracture behavior is represented by the post-necking true stress-strain curve, toughness index (resistance to fracture initiation) in the stress modified critical strain model (SMCS) and damage evolution law. It is found that different types of high-strength steels with similar yield strength may exhibit quite different fracture behavior after exposure to high temperatures. The maximum exposure temperature and cooling method are two critical factors influencing the post-fire fracture behavior of high-strength steels. The true stress-strain curves after onset of necking can be simply expressed by a straight line with a slope, which becomes temperature dependent when the exposed temperature exceeding a critical level (e.g. 600 °C). The toughness index in SMCS model is subjected to great reduction in a temperature range of 800 °C to 900 °C for Q460-Q890 steels and 750 °C to 900 °C for S460-S960 steels. The most rapid evolution of damage occurs after being exposed to temperatures in a range of 650 °C to 900 °C. Compared to air-cooling method, the water-cooling method may lead to great reduction in the slope of post-necking true stress-strain curves (by 50%), significant reduction in toughness index (by 80%), and even change of fracture mode from ductile fracture to brittle fracture. It is recommended to choose reasonable and appropriate post-fire material properties for fracture prediction of different high-strength steels.